Analysis of cohesion and collective efficacy profiles for the performance of soccer players - Leo, F. M.; Sanchez-Miguel, P. A.; Sanchez-Oliva, D.; Amado, D.; Garcia-Calvo, T. (Journal of Human Kinetics, 2013)
The principal aims of the study were to define different profiles of cohesion and perceived efficacy in soccer players and to measure their differences in performance. The subjects were 235 soccer players in the under-18 category who played in the National League in Spain and 15 coaches whose ages ranged from 29 to 45 years. Diverse instruments to assess cohesion, perceived efficacy, and expectations of success were used in the study. Moreover, we measured playing time and performance. The results of the study proved the existence of four cohesion and efficacy profiles that presented significant differences in expectations of success, playing time, and performance. Furthermore, significant differences were found in the distribution of players in the teams as a function of performance. The main conclusion of this study is that soccer players with higher cohesion and collective efficacy levels belonged to teams that completed the season at the top-level classification. In contrast, athletes with low cohesion and collective efficacy usually played in unsuccessful teams. Coaches and sports psychologists are encouraged to promote both social and task cohesion and collective efficacy to enhance team performance.